Physiological Adjustments to Stress Measures Following Massage Therapy: A Review of the Literature - Moraska, Albert (Oxford University Press, 2010)
Use of massage therapy by the general public has increased substantially in recent years. In light of the popularity of massage therapy for stress reduction, a comprehensive review of the peer-reviewed literature is important to summarize the effectiveness of this modality on stress-reactive physiological measures. On-line databases were searched for articles relevant to both massage therapy and stress. Articles were included in this review if (i) the massage therapy account consisted of manipulation of soft tissues and was conducted by a trained therapist, and (ii) a dependent measure to evaluate physiological stress was reported. Hormonal and physical parameters are reviewed. A total of 25 studies met all inclusion criteria. A majority of studies employed a 20–30 min massage administered twice-weekly over 5 weeks with evaluations conducted pre-post an individual session (single treatment) or following a series of sessions (multiple treatments). Single treatment reductions in salivary cortisol and heart rate were consistently noted. A sustained reduction for these measures was not supported in the literature, although the single-treatment effect was repeatable within a study. To date, the research data is insufficient to make definitive statements regarding the multiple treatment effect of massage therapy on urinary cortisol or catecholamines, but some evidence for a positive effect on diastolic blood pressure has been documented. While significant improvement has been demonstrated following massage therapy, the general research body on this topic lacks the necessary scientific rigor to provide a definitive understanding of the effect massage therapy has on many physiological variables associated with stress.